Three Dimensional Identification of Medial and Lateral Vestibulospinal Tract in the Human Brain: A Diffusion Tensor Imaging Study - Jang, Sung H.; Kwon, Jung W.; Yeo, Sang S. (Frontiers in Human Neuroscience, 2018)
Purpose: The vestibulospinal tract(VST) is involved in balance control and gait function. No research has identified the VST in the human brain. In the current study, we attempted to identify the medial and lateral VST in the human brain, using diffusion tensor tractography(DTT). Materials and Methods: We recruited 40 healthy volunteers for this study. For reconstruction of the medial VST, a seed region of interest(ROI) was placed on the medial vestibular nuclei in the pons and target ROI on the posteromedial medulla. For reconstruction of the lateral VST, a seed ROI was placed on the lateral vestibular nuclei of pons and the target ROI on the posterolateral medulla. Values of fractional anisotropy(FA), mean diffusivity(MD), and tract volume of the medial and lateral VST were measured. Results: The medial VST, which originated from the medial vestibular nuclei, descended through the posteromedial medulla, and terminated at the anterior funiculus of the cervical spinal cord. The lateral VST originated from the lateral vestibular nuclei, and terminated in the anterior portion of lateral funiculus, through the posterolateral medulla. The FA value of medial VST was significantly higher than that of lateral VST. In contrast, the MD value and tract volume were significantly lower than those of lateral VST(p <0.05). Conclusion: We identified the medial and lateral VST in the human brain using DTT and investigated the anatomical characteristics of the medial and lateral VST. The methodology and results of this study could be helpful to both clinicians and researchers in the neuroscience field.